INTEGRATION OF INFORMATION AND MANAGEMENT PROCESSES IN THE MANAGEMENT SYSTEM OF A MODERN ENTERPRISE - СHORNA LUDMILA; KOVALENKO, OLENA; GONCHAR, OLGA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article contains the results of research on the problems of integration of information and management processes in the management system of a modern enterprise. The issues of creation and implementation of information systems in enterprise management are considered. The following options are explored: the formation of a single management information system in accordance with certain management and information flows; automation and digitalization of the control system; integration of existing information systems in accordance with management processes. The role of the information factor in management processes is relevant. The huge amount of information, the need for its filtering and processing determines the development of rational management methods using integrated information systems. Such systems provide the ability to digitize enterprise management. Various theoretical and practical studies in such areas as data digitization, digitization of management, automation of management processes show that modern information technology allows you to create a single information environment management. Such an integrated system works as a single organism in accordance with the triggers and management events and can be used both for the enterprise as a whole and for its individual units and activities. Creating such an information environment is relevant for enterprises in various industries. The urgency of the effectiveness of such integration is also confirmed by a number of developments in various information systems and platforms, as well as the need for managers in special information modules for effective decision-making The purpose of the research is to identify problems of integration of information and management system at the enterprise and to form recommendations for the introduction of modern information technologies in enterprise management. Information flows in the management system can be divided according to the type of information, which is classified according to various criteria - primary, systematized, processed for management decisions, reporting, internal and external, reliable and reliable. Primary protected enterprise data must be stored in an information system to be reusable. The integration of information and management systems involves a systems approach (systems theory, open and information systems) and the use of such well-known economic theories as the theory of constraints, information society, knowledge economy etc. In practice, there are options for creating an enterprise management system according to the processes and algorithms embedded in the information system. Conversely, an information system can be created according to a management system or adapted on the basis of popular digital platforms. In any case, changes in the management system and adaptation of the information environment, staff training are mandatory steps in the integration of the two systems. The main stages of integration are the analysis of management and information processes and identifying the level of their compliance; determination of input and output information flows, algorithms and results of their processing; determining the level of maturity of management and information technology; analysis of business processes and information flows; changes in management processes in accordance with modern information technologies; implementation of changes together with staff training and control of digital competencies in accordance with the changes. The proposed model of integration involves the collection of data on actual management processes, communications and the use of information technology in management, their evaluation by level of maturity and inconsistency; identification of problems and goals of integration and updating of management and information system taking into account risk reduction, staff training, creating a loyal attitude to the changes in accordance with the defined goals of enterprise development. The single information management space of the enterprise allows to optimize management and information flows under the condition of a high level of business intelligence at all levels of management - from top management to the individual executor. The results of analytics can be used to optimize information and management flows or the implementation of enterprise restructuring projects.